Consenso em reumatologia pediátrica: Parte II - Definiç ão de melhora clínica para o lúpus eritematoso sistêmico e dermatomiosite juvenil - Machado, Claudia [UNESP]; Ruperto, Nicolino (My University, 2005)
Objective: To evaluate the consensus development of the core response variables for disease activity in Juvenile Systemic Lupus Erythematosus (JSLE) and Juvenile Dermatomyositis (JDM) as well as the preliminary definition of improvement for both. Methods and Results: The core response domains and variables for JSLE were: 1) disease activity global assessment by the physician = 10 cm VAS; 2) health related to quality of life = CHQ-PF50 physical score; 3) disease activity global assessment by parents/patients = 10 cm VAS; 4) kidney assessment = 24 h proteinuria; 5) global disease activity assessment by a specific and valid tool (SLEDAI or ECLAM). The preliminary definition of improvement for JSLE was: 2 of the 5 measures with at least 50% of improvement and no more than 1 worse by more than 30%, which cannot be the 24 h proteinuria. The core response domains and variables for JDM were: 1) disease activity global assessment by the physician = 10 cm VAS; 2) muscle strength assessment by a specific tool (CMAS -Childhood Myositis Assessment Scale) = 0-52; 3) functional assessment by a valid tool (CHAQ); 4) disease activity global assessment by parents/patients = 10 cm VAS; 5) health related to quality of life (CHQ-PF50 physical score); 6) global disease activity assessment by specific and valid tool (DAS -Disease Activity Score). The preliminary definition of improvement for JDM was: 3 of the 6 measures with at least 20% of improvement and no more than 1 worse by more than 30%, which cannot be the muscle strength by CMAS. Conclusions: All the variables were tested and have shown good statistical responsiveness and discriminative validity to be used in therapeutic trials.
Consensus in pediatric rheumatology: Part II - Definition of clinical improvement in systemic lupus erythematosus and juvenile dermatomyositis
Keywords: Consensus; Disease activity; Juvenile dermatomyositis; Juvenile systemic lupus erythematosus